2013
DOI: 10.4093/dmj.2013.37.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Increased Selenoprotein P Levels in Subjects with Visceral Obesity and Nonalcoholic Fatty Liver Disease

Abstract: BackgroundSelenoprotein P (SeP) has recently been reported as a novel hepatokine that regulates insulin resistance and systemic energy metabolism in rodents and humans. We explored the associations among SeP, visceral obesity, and nonalcoholic fatty liver disease (NAFLD).MethodsWe examined serum SeP concentrations in subjects with increased visceral fat area (VFA) or liver fat accumulation measured with computed tomography. Our study subjects included 120 nondiabetic individuals selected from participants of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 35 publications
5
74
6
1
Order By: Relevance
“…Concentrations of FGF21, a modulator of mitochondrial oxidative phosphorylation (43), did not differ between patients and CON, in contrast to one previous study, probably due to lower age and markedly worse glycemic control of those patients (21). Also, concentrations of the hepatokine SepP, which may be increased in obesity and NAFLD (44) and interfere with insulin signaling by inhibiting phosphorylation of key mediators in energy metabolism such as protein kinase B and AMP-activated protein kinase (45), were unchanged in patients with type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 56%
“…Concentrations of FGF21, a modulator of mitochondrial oxidative phosphorylation (43), did not differ between patients and CON, in contrast to one previous study, probably due to lower age and markedly worse glycemic control of those patients (21). Also, concentrations of the hepatokine SepP, which may be increased in obesity and NAFLD (44) and interfere with insulin signaling by inhibiting phosphorylation of key mediators in energy metabolism such as protein kinase B and AMP-activated protein kinase (45), were unchanged in patients with type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 56%
“…Paradoxically, ANGPTL6 levels are elevated in patients with type 2 diabetes or metabolic syndrome [9,10] . Similarly, circulating SEPP1 is elevated in patients who are overweight and obese, or have non-alcoholic fatty liver disease, pre-diabetes and overt type 2 diabetes [11][12][13] . Whilst the liver is sensitive to changes in nutritional status, and hepatic lipid levels can fluctuate within several days of over or underfeeding [14,15] , it is unclear whether secretion of hepatokines are sensitive to acute changes in nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In a study that was an evaluation of visceral obesity using computed tomography, a correlation between visceral obesity and SeP level was observed. [32] However, some studies have demonstrated a negative correlation between SeP level, gene expression, obesity and IR. [31] In the present study we performed a correlation analysis between SeP and anthropometric parameters, and found negative correlations between SeP and waist circumference in the patient group, and also between SeP and BMI and the percentage of adipose tissue in the control group.…”
Section: Discussionmentioning
confidence: 99%